Cultural competence for evaluators: a guide for alcohol and other drug abuse prevention practitioners working with ethnic/racial communities - Orlandi, Mario A. ed (US Dept. of Health and Human Services. Office of SubstanceAbuse, Health Administration MarylandUS, 1992)
Provides conceptual frameworks and practical suggestions for evaluators working in African-American, Hispanic, American Indian/Alaska-native and Asian/Pacific Island - American population groups.